Almonds in the diet simultaneously improve plasma α-tocopherol concentrations and reduce plasma lipids - Jambazian, Pera R.; Haddad, Ella; Rajaram, Sujatha; Tanzman, Jay; Sabaté, Joan (Journal of the American Dietetic Association, 2005)
The objective of this study was to assess the dose-response effect of almond intake on plasma and red blood cell tocopherol concentrations in healthy adults enrolled in a randomized, crossover feeding trial. Participants were 16 healthy men and women, aged 41±13 years. After a 2-week run-in period, participants were fed three diets for 4 weeks each: a control diet, a low-almond diet, and a high-almond diet, in which almonds contributed 0%, 10%, and 20% of total energy, respectively. Changes in blood tocopherol levels were assayed by high pressure liquid chromatography. Incorporating almonds into the diet helped meet the revised Recommended Dietary Allowance of 15 mg/day α-tocopherol and increased lipid-adjusted plasma and red blood cell α-tocopherol concentrations. A significant dose-response effect was observed between percent energy in the diet from almonds and plasma ratio of α-tocopherol to total cholesterol.